Enhancing activity, nutrition and mental health in overweight adolescents Stage 1 - Formative Research - McManus, Alexandra; Newton, Wendy; McManus, Jennifer; Storey, Jessica; White, James; Cuesta-Briand, B. (Centre of Excellence for Science, Seafood and Health, Curtin University, 2011)
This report discusses Stage 1 of the 'Curtin Activity, Food and Attitudes Program' (CAFAP). As a part of this research program, a tertiary hospital adolescent obesity intervention was adapted and piloted it in a community setting with clinically obese adolescents and their families. The first stage of the project refined the program and its evaluation framework based on individual, family and community enablers and barriers. This report will present the outcomes of Stage 1. It will examine the experiences of participants and discuss the understanding gained of what would encourage potential participants to become involved in CAFAP if it was available to them in their community.